Circular RNA CircPVT1 Inhibits 5-Fluorouracil Chemosensitivity by Regulating Ferroptosis Through MiR-30a-5p/FZD3 Axis in Esophageal Cancer Cells - Yao, Wenjian; Wang, Jianjun; Meng, Fanruo; Zhu, Zibo; Jia, Xiangbo; Xu, Lei; Zhang, Quan; Wei, Li (Frontiers in Oncology, 2021)
Background: CircPVT1 is demonstrated to promote cancer progression in esophageal squamous cell carcinoma (ESCC). However, the role and potential functional mechanisms of circPVT1 in regulating 5-fluorouracil (5-FU) chemosensitivity remain largely unknown. Methods: ESCC cells resistant to 5-FU were induced with continuous increasing concentrations of 5-FU step-wisely. A cell counting kit-8 assay was used to analyze the viability of ESCC cells. LDH release assay kit was used to evaluate the cytotoxicity. RT-qPCR was used to assess the expression level of non-coding RNAs and cDNAs. Luciferase was used to confirm the interaction between non-coding RNAs and targets. Western blotting was used to detect the expression of downstream signaling proteins. Flow cytometry and ferroptosis detection assay kit were utilized to measure the ferroptosis of ESCC cells. Results: CircPVT1 was significantly upregulated in ESCC cells resistant to 5-FU. Knockdown of circPVT1 enhanced the 5-FU chemosensitivity of ESCC cells resistant to 5-FU by increasing cytotoxicity and downregulating multidrug-resistant associated proteins, including P-gp and MRP1. Luciferase assay showed that circPVT1 acted as a sponge of miR-30a-5p, and Frizzled3 (FZD3) was a downstream target of miR-30a-5p. The enhanced 5-FU chemosensitivity by circPVT1 knockdown was reversed with miR-30a-5p inhibitor. Besides, the increased 5-FU chemosensitivity by miR-30a-5p mimics was reversed with FZD3 overexpression. Furthermore, knockdown of circPVT1 increased ferroptosis through downregulating p-β-catenin, GPX4, and SLC7A11 while miR-30a-5p inhibition and FZD3 overexpression reversed the phenotype by upregulating p-β-catenin, GPX4, and SLC7A11. Conclusions: These results suggested a key role for circPVT1 in ESCC 5-FU-chemosensitivity in regulating the Wnt/β-catenin pathway and ferroptosis via miR-30a-5p/FZD3 axis, which might be a potential target in the treatment of ESCC.